Síntese assimétrica dos componentes do feromônio sexual da lagarta-parda, Thyrinteina arnobia (Lepidoptera: Geometridae) - Paiva, Marcelo Montanha de (Universidade Federal de São Carlos, 2013)
The pheromones play an important role in chemical communication between alive organisms. They can be used in agriculture to pest control. The brown-caterpillar, Thyrinteina arnobia, is considered in Brazil a major pest of Eucalyptus species. The damage is caused by tree defoliation due to the attack of caterpillars. In this work the asymmetric synthesis of four stereoisomers of 3,4-epoxy-6,9-eneicosadiene, sex pheromone component of T. arnobia, was accomplished in 11 steps with an overall yield of 16 to 20%. The key step of the synthetic route involved the Sharpless asymmetric epoxidation of Z- and E-2-penten-1-ol which delivered the corresponding epoxyalcohols in 70-76% yield and 80-90% ee. Electroantennographic analysis (EAG) as well as behavioural studies in laboratory and field will be conducted to evaluate the action of these compounds in insects and possible application in monitoring and pest control.
Keywords: Feromônio; CG-EAD; Thyrinteina arnobia; Síntese; Assimétrica; Estereoisômeros; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA